Analysis of Maslahah Mursalah in the Implementation of Tetanus Toxoid Immunization as a Marriage Requirement (A Study in the Pitu Riase Sub-district, Sidrap Regency) (Jurnal Marital: Kajian Hukum Keluarga Islam, 2023)
This research discusses Maslahah Murlah's review of the implementation of tetanus toxoid immunization as a marriage requirement. By examining two problem formulations, namely; how is the implementation of tetanus toxoid immunization as a marriage registration requirement in Pitu Riase District, Sidrap Regency and how is the maslahah murrasa review of the implementation of tetanus toxoid immunization as a marriage requirement in Pitu Riase District, Sidrap Regency. This research approach is an empirical normative approach, namely research carried out by examining the implementation of legal provisions which are conceptualized as norms or rules that apply in society. Then with the qualitative descriptive method which produces descriptive data in the form of written text or other people's words. The techniques used are observation, interviews and documentation methods. The results of the research can be stated that, Firstly, the provisions of the marriage registration requirements are that prospective bride and groom couples who want to get married, especially prospective brides, are advised to carry out tetanus toxoid immunization and attach a letter of proof of the implementation of this immunization. The objectives achieved by implementing tetanus toxoid immunization include preventing the spread of tetanus which can cause damage to the nervous system that regulates breathing and also damage to other organs, resulting in death. Second, the implementation of tetanus toxoid immunization as a requirement for marriage registration in Piti Riase District, Sidrap Regency, if viewed from the perspective of maslahah al-murlah, is one of the maslahah of hajiyah, namely perfecting basic human needs in maslahah dharuriyah, in this case in order to protect or maintain offspring through the prospective bride. those who are getting married and also as in the Sadd Adz-Dzari'ah principle, namely preventive measures or closing the path to something dangerous.